Performance prediction of loop-type wind turbine. (February 2020) - Jeon, Wonyoung; Park, Jeanho; Lee, Seungro; Jung, Youngguan; Kim, Yeesock; Seo, Youngjin
An experimental and analytical method to evaluate the performance of a loop-type wind turbine generator is presented. The loop-type wind turbine is a horizontal axis wind turbine with a different shaped blade. A computational fluid dynamics analysis and experimental studies were conducted in this study to validate the performance of the computational fluid dynamics method, when compared with the experimental results obtained for a 1/15 scale model of a 3 kW wind turbine. Furthermore, the performance of a full sized wind turbine is predicted. The computational fluid dynamics analysis revealed a sufficiently large magnitude of external flow field, indicating that no factor influences the flow other than the turbine. However, the experimental results indicated that the wall surface of the wind tunnel significantly affects the flow, due to the limited cross-sectional size of the wind tunnel used in the tunnel test. The turbine power is overestimated when the blockage ratio is high; thus, the results must be corrected by defining the appropriate blockage factor (the factor that corrects the blockage ratio). The turbine performance was corrected using the Bahaj method. The simulation results showed good agreement with the experimental results. The performance of an actual 3 kW wind turbine was also predicted by computational fluid dynamics.